Meningkatkan Kualitas Layanan dan Meningkatkan Mutu Sumber Daya Manusia bagi UMKM di Desa Air Batu Kota Palembang - Riri Oktarini; Dewi Lestari; Sinta Sulistiani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting the local economy, yet many face challenges in maintaining service quality and improving human resource competence. This Community Service Program (PKM) aimed to enhance service quality and strengthen human resource capacity among MSME entrepreneurs in Air Batu Village, Palembang. The activity was carried out on May 4, 2025, involved three lecturers from Universitas Pamulang as facilitators. A total of 22 MSME participants from Air Batu Village took part in the program. The PKM implementation consisted of three stages: preparation, execution, and reporting. During the execution stage, several methods were applied, including material presentation, hands-on practice, group discussions, and question-and-answer sessions. The materials delivered focused on improving customer service, business management, and sustainable practices. The results showed an increase in participants’ understanding of service excellence, business innovation, and environmental awareness in managing MSME operations. Moreover, participants demonstrated higher motivation and capability in applying the knowledge gained to improve their business performance. This program is expected to create a positive impact on the development and competitiveness of MSMEs in Air Batu Village.